Low sensitivity of the MPT64 identification test to detect lineage 5 of theMycobacterium tuberculosiscomplex. Issue 12 (December 2018) - Sanoussi, N'Dira C.; de Jong, Bouke C.; Odoun, Mathieu; Arekpa, Karamatou; Ali Ligali, Moulikatou; Bodi, Ousman; Harris, Simon; Ofori‐Anyinam, Boatema; Yeboah‐Manu, Dorothy; Otchere, Isaac Darko; Asante‐Poku, Adwoa; Anagonou, Severin; et al.
Abstract : Purpose. : Differentiation of the Mycobacterium tuberculosis complex (MTBc) from non‐tuberculous mycobacteria (NTM) is important for tuberculosis diagnosis and is a prerequisite for reliable phenotypic drug‐resistance testing. We evaluated the performance of the rapid MPT64 antigen identification test for the detection of Mycobacterium africanum lineage 5 (MAF L5). Methodology. : Smear‐positive tuberculosis patients' sputa were included prospectively. Culture was performed on Löwenstein‐Jensen medium and, when positive, the MPT64 test and the classical para‐nitro benzoic acid susceptibility and heat‐labile catalase (PNB/catalase) identification tests were performed. The MPT64 test was repeated 14 days after an initially negative first testing. Direct spoligotyping was performed for MTBc lineage determination. Results. : In total, 333 isolates were tested for all of the methods. Three hundred and twenty‐two (96.7 %) were pure MTBc, by agreement between spoligotyping and PNB/catalase, and 11 were NTM or a mixture of MTBc/NTM. The MPT64 test conducted on day zero of culture‐positivity correctly identified most of the pure MTBc isolates (93.2 %, 300/322), but it failed to detect 24 % of the L5 isolates (18/75) versus 2 % (4/202) of the L4 ones [OR=15.6 (5.3‐45.8), P <0.0001], with improved sensitivity for L5 detection on repeat testing after 14 days. The L5‐wide non‐synonymous single‐nucleotide polymorphism in the mpt64 gene may explain the poor performance of the MPT64 test for L5. Conclusion. : The MPT64 test has a lower sensitivity for detecting L5 isolates of the MTBc, and can be considered as a first‐screening test that should be confirmed by another identification method when it produces negative results in countries with L5. Given the microbiological bias in both the isolation and identification of MAF lineages, diagnostics with high sensitivity for direct testing on clinical material are preferable.